Multifaceted effects of volatile organic compounds released by Fusarium oxysporum on Trichoderma biocontrol agents - Ningxiao Li; Ki-Tae Kim; Carl Schlagnhaufer; Seogchan Kang (Biological Control)
We investigated how volatile organic compounds (VOCs) produced by Fusarium oxysporum, a soilborne fungal species complex that infects diverse plants, affect the growth of four Trichoderma spp. and their secretion of antifungal molecules and gene expression to evaluate the involvement of VOC-mediated recognition of pathogens in biocontrol. Five VOCs commonly produced by all F. oxysporum strains analyzed, including 4-ethylanisole, 1-hexanol, 3-methyl-1-butanol, isopentyl acetate, and 2-phenylethanol, were tested. All compounds inhibited Trichoderma growth in a concentration-dependent manner, with 4-ethylanisole being the most effective. Although the degree of growth inhibition by each compound was similar among the four species, their secretion of antifungal molecules varied widely, with the degree of induction in T. virens and T. viride being higher than that in T. harzianum and T. asperellum in most treatments. Transcriptome analyses via RNA-seq after exposure to 4-ethylasniole, 3-methyl-1-butanol, isopentyl acetate, and VOCs released by three F. oxysporum strains were performed. Analysis of gene ontology (GO) terms enriched among the differentially expressed genes (DEGs) revealed that diverse processes, such as synthesizing/metabolizing various types of organic compounds, ion/carbohydrate transport, proteolysis, response to stimulus, signal transduction, chromosome organization, RNA processing, and DNA metabolism, were significantly affected. Some genes likely involved in biocontrol, such as those that perform fungal cell wall degradation, protein hydrolysis, and secondary metabolite biosynthesis, were also differentially regulated. However, the DEGs in the four species did not overlap significantly, suggesting that individual species respond distinctly to each VOC treatment. Collectively, our data suggest that Trichoderma BCAs recognize other fungi through multiple specific volatile cues and prepare for subsequent encounters. We discuss future studies needed to test this hypothesis and to uncover the mechanism underlying the VOC-mediated recognition of pathogens and the resulting modulation of diverse cellular responses.